Lexical patterns in Indonesian academic writing: a corpus-based analysis for writing assistance - Abdul Wahid (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Despite growing demands for academic publication in Indonesian higher education, many students and early-career researchers struggle with appropriate lexical usage. Objective: This study identifies lexical features that characterize proficient Indonesian academic writing through a corpus-based analysis. Method: A large corpus of journal articles and theses was analyzed using frequency, lexical bundle, and keyword analysis across sections and registers. Results: Academic texts are dominated by abstract nouns and procedural verbs, while lexical bundles show strong sectional specialization; keyword analysis highlights contrasts with non-academic texts in abstraction, impersonality, and epistemic stance. Implication: These findings support the development of corpus-informed writing instruction and tools to enhance academic literacy in Indonesian contexts. Novelty: This study integrates section-sensitive lexical analysis with register-based comparison to provide a comprehensive empirical model of academic lexical proficiency.